A kind of quick repair mortar for wet interface and preparation method thereof

By using a quick repair mortar containing cement, water-soluble polymers and modifiers in the repair of ancient buildings, the problem of insufficient bonding strength in humid environments is solved and efficient repair effects are achieved.

CN116496054BActive Publication Date: 2025-01-21SOUTHEAST UNIV
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202310332831.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-31
Publication Date
2025-01-21
Estimated Expiration
2043-03-31

AI Technical Summary

Technical Problem

The prior art is difficult to achieve efficient bonding repair in humid environments, especially in the restoration of ancient buildings. The bonding strength of traditional mortar on the humid interface is insufficient, which affects the restoration effect.

Method used

A quick repair mortar is used. Its raw materials include cement cementitious material components, sand and gravel, water-soluble polymer components and modifier components. Through rapid hydration of cement and rapid polymerization of water-soluble polymers, the wet interface is realized In situ repair below.

Benefits of technology

The mortar significantly improves the bonding strength in a humid environment, with the wet interface bonding strength increased by 1200%. It has rapid setting and high toughness, and is suitable for rapid repair of ancient buildings.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure HDA0004155419230000011
    Figure HDA0004155419230000011
Patent Text Reader

Abstract

The present invention discloses a rapid repair mortar for wet interfaces and a preparation method thereof, wherein the raw materials of the rapid repair mortar include a cementitious material component, sand and gravel, a water-soluble polymer component and a modifier component, wherein the raw materials of the rapid repair mortar are mixed and directly applied to the wet interface to be repaired, and the in-situ repair under the wet interface is achieved through the rapid hydration of cement and the rapid polymerization of water-soluble polymers. For the scene that requires rapid repair under a wet environment, the bonding strength of the currently commercially available repair materials at the wet interface is significantly reduced, which seriously affects the effect of repair and reinforcement. Therefore, the present invention will prepare a rapid repair mortar for use in a wet environment. The elastic modulus of the rapid repair mortar prepared by the present invention is close to that of an ancient brick wall, and it can have good bonding performance with a substrate even in a wet environment. Compared with unmodified mortar, the wet interface bonding strength is increased by 1200%, and it has a good repair effect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ancient building restoration, and in particular to a quick-repair mortar for a wet interface and a preparation method thereof. Background Art

[0002] Masonry structures are widely used in my country and have a long history. They are one of the main forms of existing building structures and occupy an important position in historical buildings. Due to factors such as disrepair, changes in usage functions, and increased seismic fortification standards, many masonry structures need to be repaired and reinforced. Especially when reinforcing historical and cultural relics building structures, the selection of construction technology should consider the authenticity principle, minimum intervention principle, recognizability principle, and reversibility principle of building protection. Among them, mortar replacement method is a commonly used reinforcement method.

[0003] Mortar replacement is to replace part of the low-strength mortar in the masonry structure with high-performance mortar to achieve the purpose of improving the seismic performance of the masonry structure. This reinforcement method is mainly suitable for masonry structures where the block material still has sufficient strength but the mortar performance is seriously degraded. It has the characteristics of not reducing the usable area of ​​the house and reducing the disturbance to the structure.

[0004] Chinese invention patent CN113685051B discloses a low-intervention reinforcement method for masonry structures based on rapid mortar replacement. This method uses a water jet to remove the original mortar in the mortar joints, and then uses a 3D printing head to extend into the gaps after the mortar joints are removed, and fills the repair material in a "Z" shape. This process realizes the integration of joint removal and joint repair, and efficiently removes the mortar joints without damaging the block material; it realizes low-intervention reinforcement of masonry structures based on rapid mortar replacement. However, this method will make the gaps after removal relatively moist.

[0005] Due to the particularity of water-borne bonding, the use of traditional mortar materials and some ecological materials of ancient buildings in humid or underwater environments will cause a significant decrease in bonding strength. Chinese invention patent CN110563422A discloses a repair material and construction process for cracks in blue brick walls of ancient buildings. The repair material has good compatibility with blue brick walls and low cost. However, the bonding performance of the repair material prepared by the invention is still low and the weather resistance is poor. Chinese invention patent CN104230274A discloses a material for repairing the walls of ancient buildings, which has the characteristics of good mechanical strength, high durability, resistance to wind and rain erosion, and simple construction method. However, the construction method of this material is complicated and its weather resistance needs to be improved. Chinese invention patent CN115557748A discloses a repair material for the blue brick exterior wall of an ancient building, but the material will have a small amount of cracks, powdering, hollowing, peeling, etc., and the bonding performance of the material on the wet interface is insufficient. Epoxy mortar is often used for underwater bonding and repairing. However, epoxy resin is an oil-soluble resin and can remain non-dispersible in water. However, for water-rich interfaces, it is difficult for it to break through the water layer and directly contact the substrate interface, and its interfacial bonding strength is insufficient. In addition, the curing agent in the epoxy mortar reacts with water and carbon dioxide to produce white ammonium salts, which causes the bonding strength to drop rapidly, and the engineering repair cannot achieve the desired effect, thus limiting the scope of application of epoxy mortar. Moreover, its construction process is often more complicated and difficult to construct, which not only fails to achieve the desired repair effect, but also increases costs. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a rapid repair mortar for wet interfaces; another purpose of the present invention is to provide a method for preparing a rapid repair mortar for wet interfaces.

[0007] Technical solution: The present invention provides a rapid repair mortar for wet interfaces, wherein the raw materials of the rapid repair mortar include a cementitious material component, sand and gravel, a water-soluble polymer component and a modifier component, wherein the raw materials of the rapid repair mortar are mixed and directly applied to the wet interface to be repaired, and in-situ repair is achieved at the wet interface through rapid hydration of cement and rapid polymerization of water-soluble polymer.

[0008] As a further improvement of the above scheme, the following raw materials are included in parts by weight: gelling material component: 100 parts; water-soluble polymer component: 9.65 to 19.29 parts; modifier component: 5.15 to 15.15 parts.

[0009] As a further improvement of the above solution, the cementitious material components include reference cement and sulphoaluminate cement, and the mass ratio of the reference cement to the sulphoaluminate cement is 1:3-5.

[0010] As a further improvement of the above solution, the water-soluble polymer includes a monomer, an initiator and a cross-linking agent, wherein the monomer is any one of acrylamide, calcium acrylate, sodium acrylate and acrylic acid.

[0011] Preferably, the initiator is any one of ammonium persulfate, sodium persulfate and potassium persulfate.

[0012] Preferably, the cross-linking agent is N,N'-methylenebisacrylamide.

[0013] More preferably, the ratio of monomer:initiator:crosslinking agent is 8:1.5-6:0.014-0.056

[0014] More preferably, the mass ratio of the monomer:initiator:crosslinker is 8:3:0.028.

[0015] Preferably, the modifier component includes an organosilicon defoamer and an inert carbon powder.

[0016] On the other hand, the present invention provides a method for preparing the above-mentioned rapid repair mortar for wet interfaces, the preparation method comprising the following steps:

[0017] (1) Solution A is prepared by stirring and mixing the monomer, the cross-linking agent, and water in proportion until the monomer and the cross-linking agent are completely dissolved;

[0018] (2) Pre-preparation of solution B: Stir and mix the initiator and water in proportion until the initiator is completely dissolved;

[0019] (3) Preparation of dry materials: Mix cement and carbon powder in proportion;

[0020] (4) Preparation of repair mortar: Solution A, solution B, and dry materials prepared in the above steps are mixed and stirred with standard sand and water to prepare a quick repair mortar, which is directly applied to the wet interface.

[0021] In actual projects, wet and underwater repair and reinforcement situations are often encountered, for example: underwater buildings such as water conservancy projects and bridge projects where dry maintenance conditions are very difficult to achieve; mortar replacement methods using high-pressure water jets for intelligent seam removal, in order to achieve in-situ repair without time for drying; road cracks that are in urgent need of repair due to wet interfaces caused by climate factors such as rainfall, etc. For such scenarios that require rapid repairs in humid environments, the bonding strength of currently commercially available repair materials at wet interfaces is significantly reduced, seriously affecting the effect of repair and reinforcement. Therefore, the present invention will prepare a rapid repair mortar for use in humid environments. The elastic modulus of the rapid repair mortar prepared by the present invention is close to that of ancient brick walls, and it can have good bonding properties with the substrate even in humid environments. Compared with unmodified mortar, the wet interface bonding strength is increased by 1200%, with good repair effects.

[0022] In-situ polymerization modified cement-based materials is a new modification method with significant advantages. It has incomparable advantages over traditional methods in terms of densification and toughening of cement-based materials, and has broad research and application prospects. The present invention combines organic polymer materials with inorganic cement-based materials. On the one hand, the polymerization reaction of acrylamide to polyacrylamide is an exothermic process, and cement hydration is also an exothermic process. The in-situ addition method will promote each other, thereby achieving the purpose of rapid repair; on the other hand, because polyacrylamide is a flexible hydrophilic material, the prepared mortar will make up for the problem of large brittleness of cement-based materials, the elastic modulus does not match the blue brick, and the wet interface bonding performance is insufficient, and has excellent wet interface bonding performance; and cement-based materials are low in price, stable in performance, and good in durability, so as to make up for the problem of insufficient durability of polyacrylamide, so that the advantages of both parties complement each other, which can improve the wet interface bonding performance and toughness of the mortar, appropriately reduce the compressive strength and elastic modulus to match the ancient blue brick, and at the same time have excellent fluidity, which is conducive to grouting operation and fully filling the mortar gap. In addition, the rapid repair mortar invented by this patent can effectively replace the failed mortar in the joints of ancient blue brick walls, and achieve a major "blood transfusion" of the walls without excessive intervention in the walls. While the construction is convenient and fast, it can effectively avoid unnecessary damage to the building and effectively shorten the construction period.

[0023] Beneficial effects: Compared with the prior art, the present invention has the following significant advantages: The present invention adopts polyacrylamide to modify cement mortar in situ, and obtains a rapid repair mortar for failed mortar joints of ancient buildings. On the one hand, ordinary repair mortar has weak bonding strength due to the barrier of the surface water layer of the wet interface, but the repair mortar of the present invention has been in-situ modified with a hydrophilic polymer and has excellent wet interface bonding performance; on the other hand, the in-situ modified mortar of the present invention has an extremely fast setting speed, can quickly produce a strong structure, and realize the in-situ repair of ancient buildings. The present invention adopts an in-situ modification method to improve the toughness of the mortar and the wet interface bonding performance, so that the repaired ancient buildings can be reinforced and not easily destroyed, which is of great significance for the restoration of ancient buildings. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1 The pictures are before (left) and after (right) the restoration of the blue brick exterior wall;

[0025] Figure 2 This is a schematic diagram of the wall repair process;

[0026] Figure 3 The mortar color before (left) and after (right) adding carbon powder to color; DETAILED DESCRIPTION

[0027] The technical solution of the present invention is described in detail below through specific embodiments, but it should be clearly pointed out that

[0028] These examples are provided for illustration and are not to be construed as limiting the scope of the present invention.

[0029] Example 1

[0030] This embodiment provides a rapid repair mortar for a wet interface, and its raw material components are as follows:

[0031] 20 parts of standard cement, 80 parts of sulphoaluminate cement, 300 parts of sand, 45 parts of water, 0.15 parts of organosilicon defoamer, 10 parts of carbon powder, 7 parts of acrylamide, 2.625 parts of ammonium persulfate, 0.0245 parts of N,N'-methylenebisacrylamide;

[0032] The ratio of monomer:initiator:crosslinking agent in the acrylamide composition is controlled to be 8:3:0.028;

[0033] The preparation steps of the above-mentioned rapid repair mortar are as follows:

[0034] Step (1) Solution A is prepared: acrylamide monomer, N,N'-methylenebisacrylamide crosslinking agent and water are stirred and mixed in a mass ratio of 8:0.028:20 until acrylamide monomer and crosslinking agent are completely dissolved. The dissolution process is an endothermic process and the solution must be restored to the required temperature before use.

[0035] Step (2) Pre-preparation of solution B: Stir and mix the initiator ammonium persulfate and water in a mass ratio of 3:10 until the initiator is completely dissolved. The dissolution process is an endothermic process and the solution must be restored to the required temperature before use.

[0036] Step (3) Preparation of dry materials: Mix the base cement, sulphoaluminate cement and carbon powder in proportion.

[0037] Step (4) Preparation of repair mortar: The inorganic cementitious material composition described in step 3, the acrylamide composition described in steps 1 and 2, standard sand and water are uniformly mixed according to the above proportions, and stirred at high speed for 1 minute using a cement mortar mixer to prepare a mortar composite material for rapid repair of ancient buildings.

[0038] Example 2

[0039] This embodiment provides a rapid repair mortar for a wet interface, and its raw material components are as follows:

[0040] 20 parts of base cement, 80 parts of sulphoaluminate cement, 300 parts of sand, 45 parts of water, 0.15 parts of organosilicon defoamer, 10 parts of carbon powder, 9 parts of acrylamide, 3.375 parts of ammonium persulfate, 0.0315 parts of N,N'-methylenebisacrylamide;

[0041] The ratio of monomer:initiator:crosslinking agent in the acrylamide composition is controlled to be 8:3:0.028;

[0042] The preparation method of the above-mentioned rapid repair mortar for wet interfaces is the same as that in Example 1.

[0043] Example 3

[0044] This embodiment provides a rapid repair mortar for wet interfaces, and its raw material components are as follows:

[0045] 20 parts of standard cement, 80 parts of sulphoaluminate cement, 300 parts of sand, 45 parts of water, 0.15 parts of organosilicon defoamer, 10 parts of carbon powder, 11 parts of acrylamide, 4.125 parts of ammonium persulfate, 0.0385 parts of N,N'-methylenebisacrylamide;

[0046] The ratio of monomer:initiator:crosslinking agent in the acrylamide composition is controlled to be 8:3:0.028;

[0047] The preparation method of the above-mentioned rapid repair mortar for wet interfaces is the same as that in Example 1.

[0048] Example 4

[0049] This embodiment provides a rapid repair mortar for wet interfaces, and its raw material components are as follows:

[0050] 20 parts of base cement, 80 parts of sulphoaluminate cement, 300 parts of sand, 45 parts of water, 0.15 parts of organosilicon defoamer, 10 parts of carbon powder, 11 parts of acrylamide, 2.075 parts of ammonium persulfate, 0.0385 parts of N,N'-methylenebisacrylamide;

[0051] The ratio of monomer:initiator:crosslinking agent in the acrylamide composition is controlled to be 8:1.5:0.028;

[0052] The preparation method of the above-mentioned rapid repair mortar for wet interfaces is the same as that in Example 1.

[0053] Example 5

[0054] This embodiment provides a rapid repair mortar for wet interfaces, and its raw material components are as follows:

[0055] 20 parts of standard cement, 80 parts of sulphoaluminate cement, 300 parts of sand, 45 parts of water, 0.15 parts of organosilicon defoamer, 10 parts of carbon powder, 11 parts of acrylamide, 8.25 parts of ammonium persulfate, 0.0385 parts of N,N'-methylenebisacrylamide;

[0056] The ratio of monomer:initiator:crosslinking agent in the acrylamide composition is controlled to be 8:6:0.028;

[0057] The preparation method of the above-mentioned rapid repair mortar for wet interfaces is the same as that in Example 1.

[0058] Example 6

[0059] This embodiment provides a rapid repair mortar for a wet interface, and its raw material components are as follows:

[0060] 20 parts of base cement, 80 parts of sulphoaluminate cement, 300 parts of sand, 45 parts of water, 0.15 parts of organosilicon defoamer, 10 parts of carbon powder, 11 parts of acrylamide, 4.125 parts of ammonium persulfate, 0.01925 parts of N,N'-methylenebisacrylamide;

[0061] The ratio of monomer:initiator:crosslinking agent in the acrylamide composition is controlled to be 8:3:0.014;

[0062] The preparation method of the above-mentioned rapid repair mortar for wet interfaces is the same as that in Example 1.

[0063] Example 7

[0064] This embodiment provides a rapid repair mortar for a wet interface, and its raw material components are as follows:

[0065] 20 parts of standard cement, 80 parts of sulphoaluminate cement, 300 parts of sand, 45 parts of water, 0.15 parts of organosilicon defoamer, 10 parts of carbon powder, 11 parts of acrylamide, 4.125 parts of ammonium persulfate, 0.077 parts of N,N'-methylenebisacrylamide;

[0066] In the control acrylamide composition, monomer:initiator:crosslinking agent=8:3:0.056;

[0067] The preparation method of the above-mentioned rapid repair mortar for wet interfaces is the same as that in Example 1.

[0068] Example 8

[0069] This embodiment provides a rapid repair mortar for a wet interface, and its raw material components are as follows:

[0070] 25 parts of base cement, 75 parts of sulphoaluminate cement, 300 parts of sand, 45 parts of water, 0.15 parts of organosilicon defoamer, 5 parts of carbon powder, 11 parts of acrylamide, 4.125 parts of ammonium persulfate, 0.0385 parts of N,N'-methylenebisacrylamide;

[0071] The ratio of monomer:initiator:crosslinking agent in the acrylamide composition is controlled to be 8:3:0.028;

[0072] The preparation method of the above-mentioned rapid repair mortar for wet interfaces is the same as that in Example 1.

[0073] Example 9

[0074] This embodiment provides a rapid repair mortar for a wet interface, and its raw material components are as follows:

[0075] 17 parts of base cement, 83 parts of sulphoaluminate cement, 300 parts of sand, 45 parts of water, 0.15 parts of organosilicon defoamer, 15 parts of carbon powder, 11 parts of acrylamide, 4.125 parts of ammonium persulfate, 0.0385 parts of N,N'-methylenebisacrylamide;

[0076] The ratio of monomer:initiator:crosslinking agent in the acrylamide composition is controlled to be 8:3:0.028;

[0077] The preparation method of the above-mentioned rapid repair mortar for wet interfaces is the same as that in Example 1.

[0078] Performance test of in-situ modified mortar prepared in Examples 1-9

[0079] The performance of the in-situ modified mortar prepared in Examples 1-9 was tested according to the following standards: "Test Method for Strength of Cement Mortar (ISO)" (GB / T 17671-1999), "Test Method for Mechanical Properties of High Ductility Fiber Reinforced Cement-based Composite Materials" (JC / T 2461-2018), "Repair Mortar" (JC / T 2381-2016), "Test Method for Basic Properties of Building Mortar" (JGJ / T 70-2009). The test contents mainly include: tensile bonding strength, compressive strength, flexural strength, elastic modulus, final setting time, and fluidity.

[0080] Table 1 Performance test results of the repair mortars prepared in Examples 1-9 and the unmodified mortar

[0081]

[0082]

[0083] Compared with the unmodified mortar, the in-situ modified mortar prepared in Example 1 has a 120% increase in the bonding strength of the dry interface and a 520% ​​increase in the wet interface; a 1.72% decrease in compressive strength; a 65.35% increase in flexural strength; a 17.2% decrease in elastic modulus; a 41.73% increase in fluidity; and a 21.45% shortened final setting time.

[0084] Compared with the unmodified mortar, the in-situ modified mortar prepared in Example 2 has a 196% increase in the bonding strength of the dry interface of the mortar, a 615% increase in the wet interface, a 13.09% decrease in compressive strength, a 78.42% increase in flexural strength, a 46.45% decrease in elastic modulus, a 59.06% increase in fluidity, and a 28.70% shortening in final setting time.

[0085] Compared with the unmodified mortar, the in-situ modified mortar prepared in Example 3 has a 265% increase in dry interface bonding strength, a 1200% increase in wet interface bonding strength, a 16.45% decrease in compressive strength, an 82.97% increase in flexural strength, a 54.26% decrease in elastic modulus, an 81.10% increase in fluidity, and a 26.98% decrease in final setting time.

[0086] Compared with the unmodified mortar, the in-situ modified mortar prepared in Example 4 has an 80% increase in dry interface bonding strength, a 370% increase in wet interface bonding strength, a 14.73% decrease in compressive strength, a 43.567% increase in flexural strength, a 48.58% decrease in elastic modulus, a 75.59% increase in fluidity, and a 36.25% shortened final setting time.

[0087] Compared with the unmodified mortar, the in-situ modified mortar prepared in Example 5 has a 185% increase in dry interface bonding strength, an 845% increase in wet interface bonding strength, a 18.43% decrease in compressive strength, a 71.68% increase in flexural strength, a 57.84% decrease in elastic modulus, an 85.83% increase in fluidity, and a 49.11% shortened final setting time.

[0088] Compared with the unmodified mortar, the in-situ modified mortar prepared in Example 6 has a 172% increase in the bonding strength of the dry interface of the mortar, an 850% increase in the wet interface, a 18.86% decrease in compressive strength, a 56.24% increase in flexural strength, a 50.43% decrease in elastic modulus, a 74.02% increase in fluidity, and a 35.56% shortened final setting time.

[0089] Compared with the unmodified mortar, the in-situ modified mortar prepared in Example 7 has a 209% increase in dry interface bonding strength, a 915% increase in wet interface bonding strength, a 16.19% decrease in compressive strength, a 75.45% increase in flexural strength, a 59.01% decrease in elastic modulus, an 82.68% increase in fluidity, and a 38.00% shortened final setting time.

[0090] Compared with the unmodified mortar, the in-situ modified mortar prepared in Example 8 has a 165% increase in dry interface bonding strength, a 555% increase in wet interface bonding strength, a 10.01% decrease in compressive strength, an 81.58% increase in flexural strength, a 44.68% decrease in elastic modulus, an 85.83% increase in fluidity, and a 9.54% extension in final setting time.

[0091] Compared with the unmodified mortar, the in-situ modified mortar prepared in Example 9 has a 154% increase in the bonding strength of the dry interface of the mortar, a 540% increase in the wet interface, a 19.25% decrease in compressive strength, a 70.50% increase in flexural strength, a 59.22% decrease in elastic modulus, a 71.65% increase in fluidity, and a 18.04% shortened final setting time.

[0092] Comprehensive comparison of Examples 1-9 shows that the optimal mass ratio of the benchmark cement and the sulphoaluminate cement in the cement component is 1:4; the optimal mass ratio of the monomer, the initiator and the cross-linking agent in the acrylamide composition is 8:3:0.028; and the optimal mass ratio of acrylamide to cement is 11:100.

[0093] Application Example 1: The materials in the proportion used in Example 3 were used to repair the mortar joints on the blue brick exterior wall of a century-old house in Jiangzhuang Village, Xinghua City, Jiangsu Province. The color of the mortar was similar to that of the blue bricks.

Claims

1. A rapid repair mortar for wet interfaces, characterized in that: The raw materials of the rapid repair mortar include cement binder component, sand and gravel, water-soluble polymer component and modifier component, wherein the raw materials of the rapid repair mortar are mixed and directly applied on the wet interface to be repaired, and the in-situ repair under the wet interface is achieved through the rapid hydration of cement and the rapid polymerization of water-soluble polymer; the rapid repair mortar for wet interface includes the following raw materials in parts by weight: sand and gravel: 300 parts; binder component: 100 parts; water-soluble polymer component: 9.65-19.29 parts; modifier component: 5.15-15.15 parts; the binder component: It comprises reference cement and sulphoaluminate cement, wherein the mass ratio of the reference cement to the sulphoaluminate cement is 1:3-5; the water-soluble polymer comprises a monomer, an initiator and a cross-linking agent, wherein the monomer is any one of acrylamide, calcium acrylate, sodium acrylate and acrylic acid; the initiator is any one of ammonium persulfate, sodium persulfate and potassium persulfate; the modifier component comprises an organosilicon defoamer and inert carbon powder; the cross-linking agent is N,N'-methylenebisacrylamide; and the mass ratio of the monomer:initiator:cross-linking agent is 8:1.5-6:0.014-0.

056.

2. The rapid repair mortar for wet interfaces according to claim 1, characterized in that: The mass ratio of the reference cement to the sulphoaluminate cement in the cement component is 1:4; the mass ratio of the monomer: the initiator: the cross-linking agent is 8:3:0.028; and the mass ratio of acrylamide to cement is 11:

100.

3. The rapid repair mortar for wet interfaces according to claim 1, characterized in that: The modifier component includes an organic silicon defoamer and inert carbon powder.

4. A method for preparing a rapid repair mortar for a wet interface according to any one of claims 1 to 3, characterized in that: The preparation method comprises the following steps: (1) Pre-preparation of solution A: Mix the monomer, cross-linking agent, and water in proportion until the monomer and cross-linking agent are completely dissolved; (2) Pre-preparation of solution B: Stir and mix the initiator and water in proportion until the initiator is completely dissolved; (3) Preparation of dry materials: Mix cement and carbon powder in proportion; (4) Preparation of repair mortar: Solution A, solution B, and dry materials prepared in the above steps are mixed and stirred with standard sand and water to prepare a quick repair mortar, which is directly applied to the wet interface.

Citation Information

Patent Citations

  • Material and construction technology for repairing historic building wall

    CN104230274A

  • Repairing material for ancient building black brick wall cracks and construction process

    CN110563422A

  • Low-intervention reinforcement method for masonry structures based on rapid mortar replacement

    CN113685051B

  • Repairing material for ancient building black brick outer wall and preparation method of repairing material

    CN115557748A

  • Underwater anti-dispersing quick repairing material and preparation method thereof

    CN107098661A